Pendampingan Digital Teacherpreneurship Dalam Meningkatkan Kapasitas Kewirausahaan Guru TK Berbasis Literasi Pemasaran Digital Di Kecamatan Telaga - Rahmawati Sarizki Habie; Andi Tenri Ampa; Noor Hasana Hakim; Alfiana Damasinta; Ratna S (CV. Multi Kreasi Media, 2026)
Strengthening teachers’ entrepreneurial capacity is an important strategy to encourage educators’ economic independence amid the rapid growth of the digital economy ecosystem. This community service program was conducted at a school on May 21, 2026, involving kindergarten teachers in Telaga District as the main audience. The program aimed to improve teachers’ understanding and skills in developing digital-based entrepreneurship through the concept of Digital Teacherpreneurship. The implementation method used a Participatory Action Learning (PAL) approach consisting of three stages: identifying teachers’ entrepreneurial needs, mentoring digital marketing literacy, and practicing the development of product promotion strategies using simple digital technology. Data were collected through participatory observation, group discussion, activity documentation, and evaluation of participants’ practical outputs. The results showed that Digital Teacherpreneurship mentoring improved teachers’ understanding of modern entrepreneurship, the use of digital media for promotion, product description writing, and simple marketing strategies that can be applied through laptops and social media. This activity also encouraged collective awareness that kindergarten teachers can develop economic potential ethically, creatively, and professionally without neglecting their main role as educators. Therefore, Digital Teacherpreneurship mentoring is a relevant empowerment model to strengthen teachers’ entrepreneurial literacy in the era of digital transformation.